2022
DOI: 10.1101/2022.09.07.22279527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice (KAP) study on COVID-19 among the general population of Nepal

Abstract: The COVID-19 pandemic has become one of the global health challenges in the current context. In Nepal, the first confirmed case was reported on 23 January 2020, and since then it has resulted in several negative impacts including economic disruption and deterioration of physical and mental health. In such a pandemic, it is indispensable to understand the knowledge and behavioral patterns of the general population regarding COVID-19. Therefore, our study aimed to assess the knowledge, attitude and practice on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…The present study in agreement with Shrestha et al, (2023) who aimed to know the rate of infection in semen of infertile men, and the association of seminal bacteria with semen parameters related to fertility potential. They demonstrated that sperm concentration, total motility, morphology, and vitality of the samples tends to be lower in men with bacteriospermia than in those without bacteriospermia, however the association was statistically insigni cant with p-values greater than 0.05(40). The study of Berjis et al, (2018) who aimed to determine the role of bacterial infection on semen parameters including motility, count and normal morphology in infertile male patients.…”
mentioning
confidence: 99%
“…The present study in agreement with Shrestha et al, (2023) who aimed to know the rate of infection in semen of infertile men, and the association of seminal bacteria with semen parameters related to fertility potential. They demonstrated that sperm concentration, total motility, morphology, and vitality of the samples tends to be lower in men with bacteriospermia than in those without bacteriospermia, however the association was statistically insigni cant with p-values greater than 0.05(40). The study of Berjis et al, (2018) who aimed to determine the role of bacterial infection on semen parameters including motility, count and normal morphology in infertile male patients.…”
mentioning
confidence: 99%